2022
DOI: 10.1016/j.sapharm.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce benzodiazepine and sedative-hypnotic drug use in acute care hospitals: A scoping review

Abstract: Background Benzodiazepines and sedative-hypnotics (BZD/SHD) are commonly utilized in the acute care setting for insomnia and anxiety and are associated with cognitive impairment, falls, fractures, and increased mortality. Interventions to reduce use of BZD/SHD in hospitals are not well characterized. The objective of the scoping review was to identify and characterize interventions to reduce the use of BZD/SHD by adults for anxiety and sedation in hospitals.Methods We included studies and abstracts published i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Another way of supporting deprescribing in the hospital setting would be to target practitioners’ behavior by measuring, reporting, and sharing deprescribing activity [ 49 ]. A recent scoping review on interventions implemented in the acute care setting, but not specific to older adults, reported that multifaceted interventions aimed at patients and healthcare providers that include a combination of education, sleep protocols, and deprescribing may support reductions in benzodiazepine or other sedative/hypnotic drug use [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way of supporting deprescribing in the hospital setting would be to target practitioners’ behavior by measuring, reporting, and sharing deprescribing activity [ 49 ]. A recent scoping review on interventions implemented in the acute care setting, but not specific to older adults, reported that multifaceted interventions aimed at patients and healthcare providers that include a combination of education, sleep protocols, and deprescribing may support reductions in benzodiazepine or other sedative/hypnotic drug use [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few small studies reported encouraging data showing that engaging with patients during their hospital stay may contribute to increased rates of BZRA deprescribing, but post-discharge data were reported scarce [ 15 17 ]. A scoping review from Neville et al recently identified interventions implemented in the acute care setting, but not specifically for older adults [ 18 ]. While the effects of pharmacotherapy optimization approaches on overall rates of potentially inappropriate prescribing have been measured [ 19 ], little is known about how much these global approaches can modify BZRA use during hospitalization and after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that hospitalisation may be an opportune time to review a patient's medications, educate patients and their families on the risks of benzodiazepines, 18 19 and to potentially reduce use of benzodiazepines and sedative-hypnotics. 20 A 2019 study in more than 100 Italian internal medicine and geriatric wards found that from admission to discharge, the prevalence of inappropriate benzodiazepine prescriptions decreased by 4%, demonstrating that some benzodiazepine prescriptions are identified and reduced or stopped during hospitalisation. 21 Another study in three Canadian medical centres found that an intervention using an electronic decision support tool for deprescribing led to an 5% increase in the proportion of patients who were deprescribed benzodiazepines and sedative-hypnotics from admission to discharge.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…This approach has been used with smoking cessation, where this initial pause has been leveraged as an opportunity to quit. Several studies have found that hospitalisation may be an opportune time to review a patient’s medications, educate patients and their families on the risks of benzodiazepines,18 19 and to potentially reduce use of benzodiazepines and sedative-hypnotics 20. A 2019 study in more than 100 Italian internal medicine and geriatric wards found that from admission to discharge, the prevalence of inappropriate benzodiazepine prescriptions decreased by 4%, demonstrating that some benzodiazepine prescriptions are identified and reduced or stopped during hospitalisation 21.…”
Section: Introductionmentioning
confidence: 99%
“…2,[7][8][9][10] For example, interventions have typically focused on educating providers through didactic education alone and do not account for the stress or cognitive overload faced by physicians in caring for acutely ill older adults. [10][11][12] Factors like clinical complexity, perceived pressure from nursing staff and patients, and fatigue can magnify this stress. [13][14][15] This may be especially challenging for less experienced physicians, particularly medical residents.…”
Section: Introductionmentioning
confidence: 99%